A Methodological Note on Setting-up Logging and Replay Mechanisms in InfoVis Systems - Henry Riche, Nathalie; Elmqvist, Niklas; Fekete, Jean-Daniel (In BEyond time and errors: novel evaLuation methods for Information Visualization (BELIV'08), 2008)
Information Visualization needs longitudinal studies to assess the usefulness, usability, and, more generally, the value of its techniques. However, most of the longitudinal studies conducted so far have involved human resources to collect and analyze evidences. Automatic logging and session replay mechanisms can help answering questions while limiting human collection and analysis of data. In this article, we describe how to s